Effectiveness of Dexamethasone, Methylprednisolone and Hydrocortisone Administration on LDH, CRP, D-and PaO2/FiO2 Ratio - Muhammad Zubaidi; Ira Nurrasyidah; Mohamad Isa (Berkala Kedokteran, 2023)
Abstract: Steroids are the standard recommended therapy for COVID-19, especially in critically ill patients. Previous studies have shown that steroids are beneficial for inflammatory markers such as C-Reactive Protein (CRP), Lactate Dehydrogenase (LDH) and D-dimer as well as the value of the PaO2/FiO2 ratio. This study aims to determine the differences in the effects of the steroid’s dexamethasone, methylprednisolone and hydrocortisone on inflammatory markers. This research is a retrospective cohort study. The samples were all COVID-19 patients with critical degrees from January to June 2021. The independent variables were dexamethasone, methylprednisolone and hydrocortisone. The dependent variables are CRP, LDH, D-dimer and the ratio of PaO2/FiO2. The statistical test used was the Kolmogorov-Smirnov test and continued with the Kruskal-Wallis test and the Mann-Whitney U test. A total of 148 subjects with a total sample of dexamethasone 60, methylprednisolone 55 and hydrocortisone 33. The statistical test results showed a significant difference in the effect of the steroid dexamethasone, methylprednisolone and hydrocortisone on the value of the PaO2/FiO2 ratio (p=0.04). Administration of hydrocortisone and dexamethasone was statistically superior to methylprednisolone for increasing the PaO2/FiO2 ratio.